2014
DOI: 10.1038/ncomms4139
|View full text |Cite
|
Sign up to set email alerts
|

Two potential therapeutic antibodies bind to a peptide segment of membrane-bound IgE in different conformations

Abstract: IgE mediates hypersensitivity reactions responsible for most allergic diseases, which affect 20-40% of the population in developed countries. A 52-residue domain of membrane-bound IgE (mIgE) called CemX is currently a target for developing therapeutic antibodies; however, its structure is unknown. Here we show that two antibodies with therapeutic potential in IgE-mediated allergic diseases, which can cause cytolytic effects on mIgE-expressing B lymphocytes and downregulate IgE production, target different conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…As there are only few examples in the literature describing extracellular ER retention motifs in transmembrane proteins, we can only speculate that the mIgE‐EMPD mediates a stable interaction with some ER‐resident component, probably a chaperone that might recognize the EMPD as an intrinsically unfolded domain and thus prevent ER exit of the long mIgE variant . This notion is supported by a recent report, which indicates that the EMPD is an intrinsically disordered domain that does not adopt ordered secondary structures . Since the folding process of immunoglobulins is accompanied and tightly controlled by the action of ER‐resident chaperones such as heavy chain binding protein (BiP, HSPA5) , the presence of an unfolded domain in the long εm Ig heavy chain might not be tolerated by the ER quality control system.…”
Section: Discussionmentioning
confidence: 67%
“…As there are only few examples in the literature describing extracellular ER retention motifs in transmembrane proteins, we can only speculate that the mIgE‐EMPD mediates a stable interaction with some ER‐resident component, probably a chaperone that might recognize the EMPD as an intrinsically unfolded domain and thus prevent ER exit of the long mIgE variant . This notion is supported by a recent report, which indicates that the EMPD is an intrinsically disordered domain that does not adopt ordered secondary structures . Since the folding process of immunoglobulins is accompanied and tightly controlled by the action of ER‐resident chaperones such as heavy chain binding protein (BiP, HSPA5) , the presence of an unfolded domain in the long εm Ig heavy chain might not be tolerated by the ER quality control system.…”
Section: Discussionmentioning
confidence: 67%
“…These observations indeed are not new, and the following are some examples of the spectrum of such interactions: gp120 of HIV‐1 unveils hidden epitopes in CD4 on the human membrane, leading to T‐cell activation; cryptic epitopes have been hypothesized to often emerge under conditions of high concentrations, leading to T‐lymphocyte activation/recognition as has been suggested to explain the unusual efficacy of mAb806 in cancer cells, where EGFR concentrations are known to be very high when compared with normal cells; antibodies against human growth hormones recognize cryptic eptiopes that are discontinuous; cryptic epitopes have been targeted in tumor immunotherapy; an antibody against the C‐Met receptor has recently been shown to be temperature sensitive and recognizes a buried epitope that is presented across a disulfide bridge, as in the current study of EGFR; and the antibodies rituximab and atumumab are classified as Type I antibodies against CD20 but recognize different epitopes, whereas tositumumab, which is a Type II antibody, recognizes an epitope that is similar to that recognized by rituximab . Indeed, rituximab has been shown to recognize a loop that is presented by a disulfide (as is the case for C‐Met and EGFR) together with a discontinuous motif (curiously cyclic peptides that present the major epitope on a loop are recognized by rituximab, but linear peptides with very different sequences are also recognized by rituximab); the CemX domain of the membrane‐bound IgE is the target for the development of therapeutic antibodies for allergies, with both antibodies targeting an intrinsically disordered region of CemX, yet binding to different conformations. Finally, panitumumab and cetuximab both target EGFR at regions that are distinct from that targeted by mAb806: cetuximab, a chimeric mouse/human antibody, recognizes a large spatial region of domain III in EGFR which is made up of discontinuous epitopes; panitumumab, a fully human antibody, also targets discontinuous regions of Domain III of EGFR, some of which overlap with those targeted by cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…They are attractive therapeutic tools due to their high specificity and that they can be used to target protein-protein interactions [56]. Besides, it has been shown that they are able to bind a peptide in different conformations [57]. These findings suggest that could be possible to use them over multi-conformational entities such as IDPs.…”
Section: Drug Designmentioning
confidence: 98%